Automated Water Level Control System Using IoT Under Diverse Conditions - Manullang, Ali Sahat Pardomuan; Zaky, Umar (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Water level management in pools and tanks is critical, but sensor accuracy can be compromised by dynamic surface conditions. This research presents the design and implementation of an Internet of Things (IoT) based system for automatically monitoring and controlling water levels. The system utilizes an HY-SRF05 ultrasonic sensor to measure water height and integrates with an automated valve (tap) control mechanism to maintain the level within predefined thresholds. A comparative analysis was initially performed with a Sharp GP2Y0A21YK0F infrared sensor, which was found to be unsuitable for the required short-range measurements. The primary system was then tested under four distinct water surface conditions: calm, wavy, foamy, and foamy-wavy, at target heights of 4 cm, 8 cm, and 12 cm. The system demonstrated high accuracy and responsiveness in all scenarios. A web and mobile application were also developed for real-time monitoring and remote management. This study confirms the robustness of the ultrasonic sensor for reliable water level automation, even in challenging environments.